Analysis of the relationship between human cytomegalovirus DNA and gB-1 genotype in the saliva of HIV/AIDS patients with xerostomia and salivary flow rate - Irna Sufiawati; S. Suniti; Revi Nelonda; Rudi Wisaksana; Agnes Rengga Rendati; Riezki Amalia; Isabellina Dwades Tampubolon (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Human immunodeficiency virus (HIV) infection increases vulnerability to opportunistic viral infection, including Human cytomegalovirus (HCMV) infection, that has been detected in saliva. The HCMV envelope glycoprotein B (gB) is highly immunogenic and has been associated with HCMV-related diseases. Purpose: The purpose of this study is to assess the prevalence of HCMV and gB-1 genotype in the saliva of HIV/AIDS patients and to analyse their relationship with xerostomia and salivary flow rate (SFR). Methods: This cross-sectional study involved 34 HIV/AIDS patients. Saliva was tested for the presence of HCMV DNA using PCR microarrays, and nested PCR for gB-1 genotype detection. Xerostomia was measured using a Fox’s questionnaire. Unstimulated whole saliva flow rate was measured by means of the spitting method. Results: The composition of the research population consisting of 73.5% males and 26.5% females with HIV/AIDS. HCMV was found in 64.7% of HIV/AIDS patients, while gB-1 genotype was detected in 59.1%. Xerostomia was closely associated with the presence of HCMV in saliva (p<0.05), but not with gB-1. There was no significant relationship between xerostomia and SFR rates in the research subjects with HCMV positive saliva (p> 0.05). Conclusion: The presence of xerostomia-associated HCMV in saliva was elevated among HIV/AIDS patients. Further investigation is required to identify other gB genotypes that may be responsible for xerostomia and SFR changes in HIV/AIDS patients.